Hubungan intensitas penggunaan TikTok dan kebiasaan makan dengan status overweight pada remaja di SMP Batik Surakarta - Alyra Ayu Kinanti; Muwakhidah Muwakhidah; Firmansyah Firmansyah (Poltekkes Kemenkes Aceh, 2026)
Background: Adolescents are vulnerable to nutritional problems, including overweight, which may be influenced by eating habits and social media use. TikTok is widely used among adolescents and may influence eating behavior through exposure to food-related content.Objectives: This study aimed to analyze the associations of TikTok use with eating habits and overweight status, as well as the association between eating habits and overweight status, among adolescents at Batik Junior High School, Surakarta.Methods: This quantitative cross-sectional study was conducted at Batik Junior High School, Surakarta, from April 29 to 30, 2026. The study involved 111 respondents selected using simple random sampling. TikTok use was measured using the Social Media Use Integration Scale (SMUIS), eating habits were assessed using the Food Frequency Questionnaire (FFQ), and nutritional status was determined based on BMI-for-age. The chi-square test was used to examine associations between variables, and Fisher's exact test was used when the assumptions of the chi-square test were not met, with a significance level of 5% (α = 0.05).Results: Most respondents had high TikTok use (62.2%), poor eating habits (67.6%), and normal nutritional status (55.9%). The proportion of poor eating habits was higher in the high-use group (76.8%) than in the moderate-use group (52.4%). Overweight status was more prevalent among respondents with poor eating habits (65.3%) than among those with good eating habits (0.0%). Based on TikTok use, overweight was identified in 43.5% of respondents with high use and 45.2% of those with moderate use. Significant associations were found between TikTok use and eating habits (p = 0.014) and between eating habits and overweight status (p < 0.001). However, TikTok use was not significantly associated with overweight status (p = 1.000).Conclusion: High TikTok use was associated with poor eating habits but was not directly associated with overweight status. Eating habits showed a stronger association with overweight status among adolescents.